THE ARTISTIC ACTIVITY OF THEOPHANES ΤΗΕ CRETAN IN WESTERN THESSALY AND THE EMERGENCE OF THE ‘‘CRETAN SCHOOL’’ OF PAINTING IN OTTOMAN GREECE - Vapheiades, Konstantinos (Analecta Stagorum et Meteororum, 2022)
One of the leading Cretan artists of the sixteenth century, whose production has not been thoroughly and critically examined yet, was Theophanes Strelitzas. The following article will expand our knowledge of his prolific artistic activity under monastic patronage in West Thessaly, already known from the katholikon of the Monastery of St. Nicholas Anapausas. In the first place, unpublished icons which pertain to Theophanes’s artistic idiom will be presented from ecclesiastical collections of the wider region. Based on this evidence, the article will raise questions concerning the emergence of the ‘‘Cretan School’’ of painting in Ottoman Greece. This discussion aims at a critical questioning of the prevailing art historical narrative on the Cretan style’s dissermination in Thessaly and continental Greece in general.